2014
DOI: 10.3897/zookeys.440.7803
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity census of Lake St Lucia, iSimangaliso Wetland Park (South Africa): Gastropod molluscs

Abstract: The recent dry phase experienced by the St Lucia estuarine system has led to unprecedented desiccation and hypersaline conditions through most of its surface area. This has changed only recently, at the end of 2011, with the onset of a new wet phase that has already caused a major shift to oligo- and mesohaline conditions. The estuary mouth, however, remains closed to the ocean, making the weak connection recently established between the St Lucia and the Mfolozi estuaries the only conveyance for marine recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 61 publications
1
25
0
1
Order By: Relevance
“…The observed mass-swarming phenomenon is not uncommon for S. striatus within its circumtropical range (Apte 2009, Bidgrain 2005, de Vargas Ribeiro et al 2017, and has been reported for other tropical heterobranch species as well (Rudman 2001, Perissinotto et al 2014. It is known to be locally common in sea grass beds and shallow water, particularly during mating season (Yonow 2012, Bidgrain 2005.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The observed mass-swarming phenomenon is not uncommon for S. striatus within its circumtropical range (Apte 2009, Bidgrain 2005, de Vargas Ribeiro et al 2017, and has been reported for other tropical heterobranch species as well (Rudman 2001, Perissinotto et al 2014. It is known to be locally common in sea grass beds and shallow water, particularly during mating season (Yonow 2012, Bidgrain 2005.…”
Section: Discussionmentioning
confidence: 96%
“…1): Stylocheilus striatus (Quoy & Gaimard, 1825) (Bebbington 1974, Yonow 2012. Its South African distribution extends from Mngazana in the Eastern Cape to southern Mozambique (Gosliner 1987, Perissinotto et al 2014. All these sites are further than 575 km from Bazaruto Island, with the closest sighting reported from Inhaca Island, Mozambique (Macnae and Kalk 1962).…”
Section: Notes On Geographic Distributionmentioning
confidence: 99%
“…Research on the trophic niche of these snails has, for example, found minimal evidence for direct food resource competition with native benthic macroinvertebrates (Miranda and Perissinotto 2014;Hill et al 2015). However, the exceptionally high densities reported from invaded environments may indirectly limit energy transfers within a food web (Hill et al 2015), and can result in decreased benthic macroinvertebrate biodiversity (Facon and David 2006;Perissinotto et al 2014). Native predators of gastropods may also be impacted through the replacement of native snail species as they may be unable to feed on the invader as they lack the ability to break the harder shell of T. granifera (Miranda et al 2016).…”
Section: Molluscamentioning
confidence: 99%
“…The iSimangaliso Wetland Park forms the southernmost region of the Maputaland centre of endemism and constitutes the focus of biodiversity conservation in the region ( Smith et al 2008 ). Recent ecological and biodiversity surveys of Lake St Lucia have been conducted in an attempt to update local taxonomic records, identify undescribed species, highlight the change in diversity over time, and provide illustrated and annotated checklists to use as identification tools ( Nel et al 2012 ; Peer et al 2014 ; Perissinotto et al 2014 ). Surveys have revealed the existence of an undescribed species of Potamonautes along the western shores of False Bay (Fig.…”
Section: Introductionmentioning
confidence: 99%